Tunable elastomer materials with vascular tissue-like rupture mechanics behavior. (1st September 2022) - Corti, Andrea; Shameen, Tariq; Sharma, Shivang; De Paolis, Annalisa; Cardoso, Luis
Abstract: Purpose . Laboratory models of human arterial tissues are advantageous to examine the mechanical response of blood vessels in a simplified and controllable manner. In the present study, we investigated three silicone-based materials for replicating the mechanical properties of human arteries documented in the literature. Methods . We performed uniaxial tensile tests up to rupture on Sylgard184, Sylgard170 and DowsilEE-3200 under different curing conditions and obtained their True (Cauchy) stress-strain behavior and Poisson's ratios by means of digital image correlation (DIC). For each formulation, we derived the constitutive parameters of the 3-term Ogden model and designed numerical simulations of tubular models under a radial pressure of 250 mmHg. Results . Each material exhibits evident non-linear hyperelasticity and dependence on the curing condition. Sylgard184 is the stiffest formulation, with the highest shear moduli and ultimate stresses at relative low strains ( μ 184 = 0.52–0.88 MPa, σ 184 = 15.90–16.54 MPa, ε 184 = 0.72–0.96). Conversely, Sylgard170 and DowsilEE-3200 present significantly lower shear moduli and ultimate stresses that are closer to data reported for arterial tissues ( μ 170 = 0.33–0.7 MPa σ 170 = 2.61–3.67 MPa, ε 170 = 0.69–0.81; μ dow = 0.02–0.09 MPa σ dow = 0.83–2.05 MPa, ε dow = 0.91–1.05). Under radial pressure, all formulations except DowsilEE-3200 at 1:1 curing ratio undergo circumferential stresses that remain in the elastic region with values ranging from 0.1 to 0.18 MPa. Conclusion . Sylgard170 and DowsilEE-3200 appear to better reproduce the rupture behavior of vascular tissues within their typical ultimate stress and strain range. Numerical models demonstrate that all three materials achieve circumferential stresses similar to human common carotid arteries (Sommer et al 2010), making these formulations suited for cylindrical laboratory models under physiological and supraphysiological loading.